Understanding Church growth - McGavran, Donald A. (Donald Anderson) (Grand Rapids, Mich. W.B.Eerdmans, 1990)
In this missionary classic, first published in 1970, Donald A. McGavran skillfully combines theological convictions, empirical research, sociological principles, and spiritual insights to mold a paradigm for effective evangelism strategy both at home and
Keywords: Church growth